Mineralogy and genesis of apocarbonate serpentinites of the Pitkäranta mining district, Northern Ladoga region. Part 1. Ophicalcite of the Hopunvaara ore field - Bulakh, M. O.; Baksheev, I. A.; Yapaskurt, V. O. (Litosfera (Ekaterinburg. Online), 2025)
Research subject. Serpentinites of the apocarbonate type in the contact aureole of the Salmi Batholith. Aim. Mineralogical and genetic description of the calcite-serpentine rocks of the Hopunvaara ore field. Materials and methods. Thirty samples of ophicalcite were studied using scanning electron microscopy, electron probe analysis, powder X-ray diffraction, FTIR and Raman spectroscopy, as well as differential thermal analysis. Results. The ophicalcite of the Hopunvaara ore field is represented by two types. The first variety was studied on samples from the Izvestkovyi quarry (“Lime Break”). It consists of thin-fibrous aggregates of clinochrysotile and lizardite (or only lizardite) intergrowing with calcite, with subordinate amounts of phlogopite and fluorapatite, as well as with veins of magnetite. Serpentine contains a small amount of impurities – up to 1.0 wt % FeO, up to 0.7 wt % Al 2 O 3 and not more than 0.1 wt % MnO. Calcite is chemically pure. Ophicalcite of the second type, described in the Klara mining, is composed mainly of lizardite, which forms complete pseudomorphs after crystals of forsterite and/or minerals of the humite group enclosed among a carbonate matrix. Serpentine contains 0.4–2.5 wt % FeO, 0.0–1.6 wt % Al 2 O 3 , 0.1–0.2 wt % MnO, and 0.9–2.1 wt % F. In the carbonate matrix, along with almost pure calcite, there is dolomite containing 1.4 wt % MnO. Minor minerals are represented by fluorite, phlogopite and sphalerite. Such a rock is sectioned by antigorite-carbonate-fluorite-hematite veins with cassiterite, the formation temperature of which is estimated at 300–350°C. Conclusions. The formation of ophicalcite of the first type occurred through the interaction of dolomite with acidic SiO 2 -rich 200–300°C hydrothermal solutions. The microfiber structure of apodolomite serpentine aggregates is due to the mechanism of their crystallization in a porous medium that occurs during carbonate leaching. Ophicalcite of the second type was formed as a result of serpentinization of forsterite calciphyres at the regressive stage of skarnification process at T < 370°C.